2018
DOI: 10.4102/rw.v9i1.172
|View full text |Cite
|
Sign up to set email alerts
|

Changing thoughts towards digital literacy interventions for South African entrepreneurs

Abstract: It has long been the focus of many countries around the world to see their entrepreneurs grow and to introduce interventions to assist them, as they realise the impact these entrepreneurs have on their economies. Technology is believed to be one of the biggest tools that entrepreneurs can use to assist them in growing sustainable businesses. There is an increased need for small businesses to employ information and communication technology (ICT) to enhance their businesses as part of their countries’ socio-econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
6
0
2
Order By: Relevance
“…Several previous studies also provided support for the results of this study. Previous relevant research provided direct analysis of the results of interviews in the field which revealed the formation of an entrepreneurial personality because students have had strong digital technology literacy for a long time (Oppong et al, 2020;Steyn, 2020). In addition, the teacher also provides survey data which explains that students who have always had a high interest in entrepreneurship are students who can form entrepreneurial personalities today (Schmitt-Rodermund, 2004;Setyaji et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies also provided support for the results of this study. Previous relevant research provided direct analysis of the results of interviews in the field which revealed the formation of an entrepreneurial personality because students have had strong digital technology literacy for a long time (Oppong et al, 2020;Steyn, 2020). In addition, the teacher also provides survey data which explains that students who have always had a high interest in entrepreneurship are students who can form entrepreneurial personalities today (Schmitt-Rodermund, 2004;Setyaji et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The hope of being accepted into the world of work is certainly not a mistake, but it cannot be denied that job opportunities are very limited and not directly proportional to graduates of higher education institutions (Usman & https://equatorscience.com/index.php/jabter Simare Mare, 2020). In addition, the government is expected to make efforts through educational policies to change the paradigm so that students are more prepared for entrepreneurship and graduates do not only focus on becoming employees (Khayru et al, 2021;Steyn, 2020). Entrepreneurship is a choice to overcome the increasing unemployment problem.…”
Section: Introductionmentioning
confidence: 99%
“…Esto se convertía en un estilo de vida que acabaría cambiando sus relaciones y dinámicas familiares. Steyn [14] en su artículo científico destacaron que la mayoría de los emprendedores ahora tenían acceso a un consultor o experto en tecnología de la información que podía ayudarlos a adquirir una mayor alfabetización digital.…”
Section: Introductionunclassified